Electrochemical study on Activated Carbon Electrode from Kenaf biowaste for Supercapacitor Application - Thilageshwaran S.; Ansari M.N.M.; Afeefah Nordin N.; Bassam A.; Yahya Z.; Elumalai P.; Prasath A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Activated carbon; Capacitance; Carbonization; Chemical activation; Climate change; Hemp; Kenaf fibers; Potassium hydroxide; Supercapacitor; Activated carbon electrode; Electrochemical studies; Electrochemical testing; Kenaf natural fibers; Optimal temperature; Specific capacitance; Supercapacitor application; Supercapacitor electrodes; Electrochemical electrodes